A hermeneutic study of integrating psychotherapist competence in postnatal child health care: nurses' perspectives - Katarina Kornaros; Sofia Zwedberg; Eva Nissen; Björn Salomonsson (BMC, 2018)
Abstract Background There is a considerable prevalence of and an increasing attention to emotional problems in families with infants. Yet, knowledge is scant of how to create efficient and accessible mental health services for this population. The study qualitatively explored public health nurses' conceptions of a clinical project, in which psychotherapists provided short-term consultations and supervisions for nurses at Child Health Centres in Stockholm. Methods In-depth interviews with fifteen nurses. The guideline of the interviews contained open-ended questions that were analysed applying a hermeneutical approach. Results Four main themes crystallized; The nurses' conceptions of their psychosocial work, Trespassing on another professional role, Interprofessional collaboration at the Child Health Centre, and The nurses' conceptions of the psychotherapist's function. In a second step, an analysis that clustered the nurses' attitudes towards handling mental health problems yielded one last theme with three "Ideal types"; nurses who expressed "I don't want to", "I want to but I cannot", and "I want to and I can" (take care of families' emotional problems at the CHC). Conclusion The nurses appreciated the easy referral and accessibility to the psychotherapists, and the possibilities of learning more about perinatal mental illness and parent-infant interactions. For a successful cooperation with the nurses, the therapist should be a team member, be transparent about his/her work, and give feedback about cases in treatment. The study also shows how the organization needs to clarify its guidelines and competence to improve psychological child health care. The paper suggests improvements for an integrated perinatal mental health care.